2018
DOI: 10.32677/ijch.2018.v05.i09.010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cord blood lipid profile in neonates and its correlation with birth weight and maternal anthropometry

Abstract: Introduction: Serum lipid disorders have their roots in childhood and atherogenic changes are postulated to originate early in life. Cord lipid profile is a useful tool in the earlier detection of babies at a higher risk. Objectives: The objectives of the study were to assess the early onset dyslipidemia by determining cord blood lipid profile in healthy term newborns and to compare the cord blood lipid profile between terms small for gestational age (SGA) and appropriate for gestational age (AGA) newborns. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Also, the study by Ramy et al showed that there was a strong negative correlation between birth weight and each of TG and LDL. 25,26 The effect of maternal serum lipid profile on neonatal outcome has been studied before but showed varied results. Ghiasi et al found a positive correlation between maternal and neonatal serum total cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the study by Ramy et al showed that there was a strong negative correlation between birth weight and each of TG and LDL. 25,26 The effect of maternal serum lipid profile on neonatal outcome has been studied before but showed varied results. Ghiasi et al found a positive correlation between maternal and neonatal serum total cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study by Ramy et al showed that there was a strong negative correlation between birth weight and each of TG and LDL. 25 26…”
Section: Discussionmentioning
confidence: 99%
“…This is related to maternal pre-BMI and GWG. 14,15,16) There is insufficient evidence to point out the relationship between maternal weight changes, birth weight and steroid hormone metabolism. Furthermore, the reason behind the altered lipid profile is not well understood.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…have shown similar findings of decreased HDL-C levels in neonates with maternal BMI ≥25 kg/m2. 14,26) Increased LDL-C, VLDL-C, triglycerides, and cholesterol levels were seen in LBW/SGA and LGA babies but there was no significant correlation with HDL-C levels 27,28) A c c e p t e d…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 1 more Smart Citation